An energy analysis comparing biomass torrefaction in depots to wind with natural gas combustion for electricity generation. (1st October 2016) - Parkhurst, Kristen M.; Saffron, Christopher M.; Miller, Raymond O.
Highlights: A torrefaction bioenergy system is compared to wind with natural gas combustion in terms of heat and power production. Torrefaction has a larger EROI for a functional unit of 100 MWe and 50 MWth . Biomass rich areas benefit from torrefaction if average wind speeds are less than 9 m/s. Consistent wind velocities exceeding 10 m/s advantage a wind-natural gas energy system. Abstract: Biomass torrefaction and wind power with natural gas are compared to determine which renewable energy system to adopt when both plant biomass and wind are available. The renewability of both systems was compared in terms of energy return on investment (EROI) by quantifying the fossil energy input and renewable energy output. On the basis of a functionally equivalent amount of electrical power (100 MWe ) and heat (50 MWth ), a breakeven wind velocity of 9.875 m/s resulted in both systems having the same EROI. In regions with available biomass feedstock, facilities suitable for biomass power and wind velocities below 9 m/s, torrefaction is a more renewable approach. Conversely, regions with velocities greater than 10 m/s or little access to biomass sources and facilities, wind combined with natural gas is superior. Due to average wind speeds below 10 m/s and the wide availability of biomass in Michigan, the torrefaction bioenergy system outperforms the wind–natural gas system.